Late Byzantium Reconsidered (Milton)
1 online resource (242 p.)
Keywords: Late Byzantium Reconsidered offers a unique collection of essays analysing the artistic achievements of Mediterranean centres linked to the Byzantine Empire between 1261, when the Palaiologan dynasty re-conquered Constantinople, and the decades after 1453, when the Ottomans took the city, marking the end of the Empire. These centuries were characterised by the rising of socio-political elites, in regions such as Crete, Italy, Laconia, Serbia, and Trebizond, that, while sharing cultural and artistic values influenced by the Byzantine Empire, were also developing innovative and original visual and cultural standards. The comparative and interdisciplinary framework offered by this volume aims to challenge established ideas concerning the late Byzantine period such as decline, renewal, and innovation. By examining specific case studies of cultural production from within and outside Byzantium, the chapters in this volume highlight the intrinsic innovative nature of the socio-cultural identities active in the late medieval and early modern Mediterranean vis-aa-vis the rhetorical assumption of the cultural contraction of the Byzantine Empire.